Molecular mechanisms and therapies for tumor inhibition through the arginine metabolism pathway - Xu, Yuhang; Yu, Mingxin; Zhang, Yi; Jiang, Yiqing; Zhu, Haiyan; He, Shujuan; Yu, Guohua; Li, Niannian; Liu, Shuzhen; Liu, Bin (Frontiers in Oncology, 2026)
Tumors are one of the major diseases leading to human death. Arginine metabolism plays an important role in tumor occurrence and metastasis. Based on the levels of arginine in tumor cells, methods such as recombinant arginine deiminase are used to reduce arginine in order to inhibit tumor growth. However, arginine deprivation therapy has limited efficacy in tumor cells due to increased arginine synthesis, resistance to chemotherapeutic agents, metabolic reprogramming, and the suppression of immune cells in the tumor microenvironment. Meanwhile, with the revelation of many new molecular mechanisms by which arginine controls tumor cell growth, numerous newly designed molecules targeting arginine metabolic pathways for cancer treatment have emerged. In this review, we integrate and analyze the responses of tumor cells and immune cells such as T cells to arginine and strategies for cancer therapy. At the molecular level, we review and discuss the mechanisms of specifically blocking arginine-regulated metabolic reprogramming in cancer cells, the effector factors from pathogenic microorganisms and metabolites from plants in inhibiting cancer cells via arginine metabolism, and arginine tRNA metabolic pathway. Finally, we discuss the mechanisms and case studies of using antineoplastic agents that target arginine metabolic pathways in combination. This review collects and integrates the mechanisms and experiences of treating various cancers through arginine and its metabolic derivatives, providing direct therapy guidance for cancer patients with disordered arginine metabolism in the tumor and immune cells.